Pendeteksian Kandungan Boraks pada Makanan yang Dijajakan di Desa Cangkarman Kabupaten Bangkalan Menggunakan Ekstrak Kunyit atau Ekstrak Bawang Merah - Erliyanti, Nove Kartika; Yoghaswara, Rachmad Ramadhan; Saputro, Erwan Adi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
This community service activity aims to give an education and training for public about the detection of borax content in foods. Borax can be detected in street foods by a special reagent containing turmeric or red onion extract. The partner of this activity is Kelompok Wanita Tani Anggrek from Desa Cangkarman, Kecamatan Konang, Kabupaten Bangkalan. This coaching consists of lecture, discussion, and workshop about borax content in sample foods. Borax can be detected by jabbing a toothpick that had been soaked in a special reagent into a sample food. The result of this activity is the partner can find out how to detect a borax content in street food around them with cheap and simple method.